Comparison of Anterior Nasal Packing versus Quilting Sutures after Septoplasty in Controlling Postoperative Bleeding - Nazir, Arooba; Ahmad, Manzoor; Kayani, Sidra Saleem; Naqvi, Bushra (Indus Journal of Bioscience Research, 2025)
Background: Septoplasty is commonly performed surgical procedure for correction of deviated nasal septum. Postoperative bleeding is frequent complication which may affect recovery and patient comfort. Different techniques like anterior nasal packing and quilting sutures are used to control bleeding after surgery. Objective: To compare anterior nasal packing and quilting sutures after septoplasty in controlling postoperative bleeding. Study Design: Randomised controlled trial. Duration and Place of Study: This study was conducted from 10th June 2024 to 10th December 2024 in Department of ENT, Combined Military Hospital Muzaffarabad. Methodology: Total 60 patients of both genders aged 18–40 years were included and randomly divided into two groups with 30 patients in each group. Group A underwent septoplasty followed by anterior nasal packing while Group B underwent quilting sutures. Postoperative bleeding was assessed within 48 hours and defined as blood loss ≥50 mL. Data was analysed using IBM SPSS version 26. Results: Mean age was 29.67±6.93 years in Group A and 29.63±6.47 years in Group B. Postoperative bleeding occurred in 3 (10.0%) patients in anterior nasal packing group and 7 (23.3%) patients in quilting sutures group (p=0.299). Majority patients had no bleeding, 27 (90.0%) in Group A and 23 (76.7%) in Group B. Significant association was observed in patients aged ≤30 years (p=0.012). Conclusion: Anterior nasal packing and quilting sutures showed comparable results in controlling postoperative bleeding. Anterior nasal packing showed better haemostasis while quilting sutures provided acceptable outcomes.